Assessment of Crop Loss Due to Elephant Crop Raids and Its Eco Friendly Mitigation - Naik, Mohan I; K, Ravikiran; A V, Basavadarshan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The crop raiding by elephants is one of the important concern causing loss of livelihood and affects the farmer’s economy. Hence a study was conducted to estimate the crop losses and to evolve an economically feasible mitigation measures. The studies were conducted in villages belonging to Kodihalli and Uyyamballi Hobli of Kanakapura Taluka, Ramanagara District, Karnataka which is surrounded by thick forest cover during 2022 to 2023. The estimation on crop loss revealed that the highest crop losses were recorded in banana (5.26 to 46.54%) plantations followed by maize (2.47 to 41.87%), ragi (2.31 to 38.95%), mango (1.28 to 32.54%), pigeon pea (1.31-21.41%) and cowpea (1.46 to 12.68%). The highest economic loss was recorded in banana and mango crops. The evaluation of mitigation measures in ragi and maize crop revealed the use of bioacoustics and predator deterrent lights provided better economical feasible mitigation measures with the cost benefit ratio of 1:2.9 and 1:3.5 respectively. The use of barbed wire fence and use of solar fence (Agri solar) was also found effective in mitigating the crop raids by elephants. However, these mitigation measures are short term and has to be used in vulnerable stages of the crop only.